Moderating effects of media towards repurchasing functional food / Mohamad Luqman Mohamad Idris ... [et al.] - Mohamad Idris, Mohamad Luqman; Tamby Chik, Chemah; Hazman Wong, Nurul Farah Sharini; Abdul Rahman, Abdul Rais; Mohd Shahril, Aslinda; Bachok, Sabaianah (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2022)
This study aims to assess how functional food attributes and media marketing influence consumers' repeat purchases. Functional food attributes include perceived value, necessity, confidence and safety while media marketing as moderating factor was studied through 2 dimensions which are communication and the internet. Survey questionnaires were distributed to 384 respondents in Petaling Jaya, Selangor, which is located approximately 10 km west of Kuala Lumpur, the capital of Malaysia. The data were analysed using Pearson correlation and linear regression. The results indicated that a significant relationship existed between functional food attributes and consumers' repeat purchases. Media marketing was found to have a strong moderating role in the relationship between functional food attributes and consumers' repeat purchases. Thus, a proper understanding of media marketing will enable manufacturers to develop better strategies for boosting sales and retaining frequent consumers. Academically, the results could improve the knowledge on functional food users and the method they acquire knowledge on functional food.